Causal Relationship Model, Sustainable Supply Chain Performance of Community Enterprises Cannabis Production Industry of Thailand - Anantarak , Phuwakorn; Toomphol, Aeknaree (Ph.D. in Social Sciences Journal, 2026)
This research article aims (1) To analyze the components and relationships of causal factors for the sustainable supply chain management performance of community enterprises in the cannabis production industry in Thailand. (2) To analyze the causal influence of economic supply chain management practices, environmental supply chain management practices, social supply chain management practices and sustainable supply chain management practices that affects the performance of sustainable supply chain management of community enterprises cannabis production industry of Thailand. (3) To present a causal relationship model for the sustainable supply chain management performance of community enterprises cannabis production industry of Thailand. This research design was a mixed-method research approach. Data were analyzed using the Structural Equation Model (SEM) technique and descriptive statistics using in-depth interviews. Data were collected using questionnaires with community enterprise administrators in the cannabis production industry of Thailand, totaling 285 locations. Findings are as follows: Social supply chain management practices, economic supply chain management practices and environmental supply chain management practices have positive indirect influences on sustainable supply chain management performance, respectively. with sustainable supply chain management practices as a mediator variable. And sustainable supply chain management practices has a positive influence on sustainable supply chain management performance. And found that the hypothetical model is consistent with the empirical data. Passed the Absolute Fit Index analysis criteria. P-value=0.051, ()=1.559, GFI=0.963, AGFI= 0.919, CFI=0.965, RMSEA= 0.044 and RMR=0.009